Kuantum Takdir: Integrasi Prinsip Ketidakpastian Heisenberg dan Konsep Takdir dalam Kosmologi Islam - Arrazi, Najib Cholil (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
In the world of modern science, Heisenberg's uncertainty principle states that at the quantum level, it is impossible to know the exact position and momentum of a particle simultaneously. Meanwhile, in Islam, the concept of destiny implies the belief that everything has been written by Allah SWT since the beginning of time (before the creation of the universe). From first glance, these two concepts seem contradictory: one emphasizes probabilistic freedom, and the other divine determinism. While the other affirms the other. This article will try to build a quantum theological model that integrates Heisenberg's uncertainty principle as a physics metaphor to understand how destiny and effort can be seen from the point of view of cosmology and epistemology. Using an interdisciplinary approach between quantum physics and Islamic theological thought, this article offers a new framework for understanding the relationship between human autonomy and divine plan.